1990
DOI: 10.1259/0007-1285-63-750-456
|View full text |Cite
|
Sign up to set email alerts
|

Radiological features of extraskeletal Ewing sarcoma

Abstract: The radiological features of extraskeletal Ewing sarcoma were reviewed in 22 patients whose average age was 22 years. Tumours were located in the extremities (11 patients), abdomen or pelvis (six patients) and the chest (five patients). The tumours ranged in size from 2 cm to 20 cm, were mainly well circumscribed and showed no evidence of calcification prior to treatment. Most tumours (13 out of 14) were of low attenuation or contained areas of lower attenuation than muscle on computed tomographic examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
14

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 12 publications
3
55
0
14
Order By: Relevance
“…L'aspect bien limité de la tumeur n'est pas synonyme de bé nignité . La lé sion est excentré e par rapport à l'os et l'atteinte osseuse est rare, secondaire, par contiguïté , lytique et/ou avec ré action pé riosté e (Rose et al [19], Kobos et al [12] [15]), l'histiofibrosarcome, le liposarcome (â ge supé rieur à 30 ans, graisse bien diffé rencié e (O'Keeffe et al [15]). Enfin, l'hé mangiopé ricytome, l'angiosarcome (Allam et al [1]) et le neurinome.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…L'aspect bien limité de la tumeur n'est pas synonyme de bé nignité . La lé sion est excentré e par rapport à l'os et l'atteinte osseuse est rare, secondaire, par contiguïté , lytique et/ou avec ré action pé riosté e (Rose et al [19], Kobos et al [12] [15]), l'histiofibrosarcome, le liposarcome (â ge supé rieur à 30 ans, graisse bien diffé rencié e (O'Keeffe et al [15]). Enfin, l'hé mangiopé ricytome, l'angiosarcome (Allam et al [1]) et le neurinome.…”
Section: Discussionunclassified
“…L'ultrastructure est de type mé -senchymateux, avec absence de structures spé cifiques comme les myofibrilles ou les granules neurosé cré tants (Allam et al [1], O'Keeffe et al [15], Enzinger et al [10]). Cet aspect rapproche le sarcome d'Ewing des tumeurs neuroectodermiques primitives (PNET).…”
Section: Discussionunclassified
“…Computed tomography scan may show a low attenuation mass with heterogeneous enhancement with contrast administration. MRI findings include signal iso-intense to muscle on T1-W images and hyper intense on T2-W images with heterogeneous enhancement after gadolinium administration 4 . The histological image of EES is a small, blue, round cell with a scanty cytoplasm and it is often confused with other small round cell tumours, but recent advances in immunohistochemistry have helped in diagnosis of ESS.…”
Section: IIImentioning
confidence: 99%
“…However, more recent studies have shown that both entities have the same molecular genetic abnormality and share immunophenotypic similarities that make them indistinguishable from each other. More commonly skeletal, the extraskeletal form is much rarer, seen in the paravertebral regions, thoracic wall (formerly known as Askin tumor), retroperitoneum, and lower extremities in older children or young adults (64). It is seldom seen in children of Asian or African descent (49).…”
Section: Ewing/primitive Neuroectodermal Tumorsmentioning
confidence: 99%